PERANCANGAN SISTEM INFORMASI INFENTARIS SPAREPART HANDPHONE BERBASIS PHP DAN MYSQL DI PLANET PHONE - Dwi Ratna Sari, Fitriani; Suryana, Amin (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2019)
Research that the author did aim to know how to design inventory system on Planet Phone.The method used is quantitative descriptive method. Data collection techniques used are literature study, observation, and interviews. From the research conducted found that there is a problem on inventory data processing. The process of inventory data processing only by writing using a general ledger. So this causes inaccuracies and delays in reports. Therefore the authors make the information system by using PHP and MySQL database. This system consists of inputting inventory data, inventory reports, sales reports and income reports. As for some suggestions given to tackle the problem is by connecting the system with internet connection, for employees more quickly and effectively in penginputan inventory data and owner can also know the sales reports and income reports more quickly without having to come directly to the store.